Acidic hydrolysis of recycled polyethylene terephthalate plastic for the production of its monomer terephthalic acid. Issue 1 (February 2023) - Islam, Muhammad Saiful; Islam, Zahidul; Hasan, Rashed; Islam Molla Jamal, AHM Shofiul
Post-consumer polyethylene terephthalate (PET) plastic bottles, after some pre-processing, were chemically depolymerized for the production of terephthalic acid (TPA), an important monomer of PET resin. The optimized condition of PET hydrolysis was 100°C with 80% v/v aqueous sulfuric acid liquor for 30 min reaction time. The terephthalic acids (TPAs) were filtered out from the reaction mixtures with a sintered glass filter. The viscosity of recycled hydrolysis liquor was measured before it was used in a successive batch of PET depolymerization. The viscosity of hydrolysis liquor increased gradually from 5 mm 2 /s to 87 mm 2 /s. TPA yields were obtained from 85.03 ± 0.03% to 99.20 ± 0.06% and the color of TPA changed from bright white to off-white in the final batches. The structure of TPA was confirmed by FTIR, mass analysis, and 1 H-NMR spectroscopy. The purity of TPA was found to be 95–98% from the HPLC study via external calibration technique. Thermogravimetric analysis (TGA) determined the thermal degradation patterns of TPAs and residual weights. This experiment reveals that repeated use of sulfuric acid hydrolysis liquor would be a good option for PET depolymerization in terms of resource utilization, TPA quality as well as sustainability. Graphical Abstract